(untitled) - Dusik, Jiri (Washington, DC, 2009)
This report describes recent progress with SEA in the region. It reviews and compares SEA practice of seven countries, examines fifteen selected SEA cases from across the region and provides a series of recommendations for further development of SEA in the region.
Keywords: Environmental impact analysis,Strategic planning,Trung tâm Học liệu ĐHCT; Environmental aspects,Phân tích khía cạnh môi trường,Kế hoạch chiến lược; Developing countries,Southeast Asia,Southeast Asia,Phát triển đất nước,Đông Nam Á,Đông Nam Á